Inovasi Pengelolaan Tutup Botol Bekas Menjadi Barang Sebaguna Menuju Sekolah Adiwiyata - Midya Yuli Amreta; Nurul Afidah; Della Nisa'ul Mufida; Ira Rahmawati; Luluk Nurul Aini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Plastic waste, especially bottle caps, is a crucial environmental problem in school environments. Although the Adiwiyata Program has been implemented, obstacles are often encountered in the form of a lack of applicable, interesting, and educational waste management innovations for students. This study aims to develop and evaluate innovations in managing used bottle caps into multipurpose items (sorting trash cans and tissue boxes) as a real contribution towards Adiwiyata Schools. Using a qualitative approach with a case study method involving four main stages: (1) problem identification through interviews and observations; (2) collection of raw materials and designing a participatory design with the theme "Watermelon"; (3) product fabrication with student involvement; and (4) implementation, socialization, and evaluation. The results of the study showed that from 2,400 used bottle caps (8.2 kg), 6 units of sorting trash cans and 10 units of tissue boxes were successfully produced. The utilization rate of new trash cans reached 85% with waste sorting accuracy increasing from 45% to 72%. Students' understanding of the upcycling concept increased significantly, from 20% to 88%. This innovation has proven effective as both an infrastructure and an educational tool, strengthening the four pillars of the Adiwiyata program. In conclusion, transforming used bottle caps into functional products through a participatory approach and attractive design is an effective strategy for addressing the plastic waste problem while strengthening environmental character education in schools, in accordance with circular economy principles.